2014
DOI: 10.1111/ijfs.12595
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bread‐making process factors on Australian sweet lupin‐wheat bread quality characteristics

Abstract: Summary Factorial experimental design was used to investigate the effects of: sponge proofing time (min), sponge and dough mixing time (min), final proofing time (min), final proofing temperature (°C) and baking time (min) on Australian sweet lupin‐wheat bread physical attributes. Factorial models show that bread specific volume was positively associated with sponge and dough mixing time (P = 0.01) and baking time (P = 0.02). Crumb area was positively associated (P = 0.01) with sponge and dough mixing time. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…Abnormal water absorption of the dough, due to the addition of fiber, results in inferior viscoelastic properties of the dough as the dough has increased water-holding abilities. Therefore, increasing the fiber amount could reduce dough stability (Villarino et al, 2014). However, cereal β-D-glucans are useful substances in functional food preparation, especially in the bakery, because of their excellent rheological properties (Sadiq Butt et al, 2008), which are confirmed in the study.…”
Section: Dough Rheologysupporting
confidence: 69%
“…Abnormal water absorption of the dough, due to the addition of fiber, results in inferior viscoelastic properties of the dough as the dough has increased water-holding abilities. Therefore, increasing the fiber amount could reduce dough stability (Villarino et al, 2014). However, cereal β-D-glucans are useful substances in functional food preparation, especially in the bakery, because of their excellent rheological properties (Sadiq Butt et al, 2008), which are confirmed in the study.…”
Section: Dough Rheologysupporting
confidence: 69%
“…Ten kg of Coromup seeds harvested in 2012 at Geraldton, Western Australia were vacuum packed in moisture-proof plastic bags, and stored at~10 C until use. The seeds were de-coated and milled as previously reported (Villarino, Jayasena, Coorey, Chakrabarti-Bell, & Johnson 2014), into flours of three differing target particle sizes (1) 120 mm screen to give 27 mm volume weighted mean particle size; (2) 750 mm screen to give 357 mm volume weighted mean particle size; and (3) 2000 mm screen to give 687 mm volume weighted mean particle size. Screen sizes were determined by preliminary milling experiments.…”
Section: Raw Materialsmentioning
confidence: 99%
“…Screen sizes were determined by preliminary milling experiments. Particle size was determined by laser light scattering using a Mastersizer 2000 (Malvern Instruments Ltd, Malvern, UK) as previously reported (Villarino et al, 2014). Flour samples were vacuum-packed in plastic bags and stored in moisture-tight boxes at~10 C until use.…”
Section: Raw Materialsmentioning
confidence: 99%
See 2 more Smart Citations